GERUND IN ENGLISH: A Morpho-Semantic Note for EFL Learners in Indonesia - Jufrizal Jufrizal; Lely Refnita (Lingua Didaktika: Jurnal Bahasa dan Pembelajaran Bahasa, 2021)
Two questions are to answer as the basis for data analysis and discussion, namely: (i) does English gerund belong to nominalization or verbalization?; and (ii) why do EFL learners in Indonesia academically need to understand the morpho-semantic properties of the English gerunds? The data presented and analyzed in this paper were collected by means of a short-limited research in the form of library study and supported by writers’ experience as the lecturers of English Grammar and Linguistics. The data analysis and discussion are based on relevant linguistic theories of morpho-syntactic properties of gerunds and those which belong to the principles of Pedagogical Grammar of EFL. The result of data analysis reveals that gerund in English is both nominalization and verbalization with certain morpho-semantic characteristics. As English gerunds are practically productive and linguistically unique, the EFL learners in Indonesia undoubtedly need the linguistic-grammatical knowledge and they are proceeded to have the ability to use gerunds grammatically. The idea delivered through this paper is believed as a significant note for EFL learners, particularly in Indonesia.